Base mediated regioselective synthesis of highly functionalized conjugated enones. Issue 37 (9th September 2015) - Singh, Surjeet; Panwar, Rahul; Althagafi, Ismail; Sharma, Vashundhara; Chaudhary, Sandeep; Pratap, Ramendra
Graphical abstract: Abstract: A simple, regioselective, convenient, and base mediated synthesis of (2 E, 4 E )-5-aryl-6-oxo-6-phenyl-3- sec. amino-hexa-2, 4-dienenitriles has been achieved by the reaction of 6-aryl-4- sec. amino-2-oxo-2 H -pyran-3-carbonitriles and benzyl cyanide. This reaction involves ring opening of the pyran ring at the C6 position by benzyl cyanide followed by decarboxylation and regioselective oxidative decyanation in the presence of atmospheric oxygen and base to afford the desired product. Proposed mechanism has been supported by isolation of the anticipated intermediate under nitrogen atmosphere. Structure and geometry of the synthesized product was confirmed by single crystal X-ray technique.